The Relationship of the Level of Knowledge About Leprosy and Self Care Agency in Leper Patients at The Leper Poly, Daha Husada Hospital, Kediri - Titik Juwariyah; Anik Nuridayanti; Suhartini (Kirana Publisher (KNPub), 2022)
Leprosy (Leprosy) is a chronic infectious disease caused by Mycobacterium leprae. This disease primarily affects the skin, peripheral nerves, and eyes. The purpose of the study was to determine the relationship between the level of knowledge about leprosy (leprosy) and self care agency in leprosy patients at the leprosy clinic, Daha Husada Hospital, Kediri. The research design used was analytical observational with a cross sectional approach. The population is all leprosy patients in the leprosy polyclinic as many as 80 respondents taken by cluster random sampling The independent variable is self care agency and the dependent variable is the level of knowledge. Data collection using a questionnaire and observation with an ordinal scale, analysis using the Rho sperm test with alpha <0.05. The results of the study from 40 respondents showed that almost all of the knowledge levels were lacking as many as 21 respondents (62.5%) had less self-care agencies, and a small part of the respondents who had sufficient knowledge levels as many as 6 Respondents (3.7%) had self-care for the good one. The results of the analysis using the Spearman Rho test obtained a p-value = 0.003 at a significant level ( α ) = 0.05, with a correlation = 0.986 and, it can be concluded that there is a significant relationship between knowledge levels and Self Care Agency in leprosy patients.The conclusion is the lower the level of patient knowledge, the less ability of leprosy patients in self care agencies. The higher the level of knowledge about leprosy, the better the self care agency.